Analisis Pelaksanaan Program Unit Kesehatan Sekolah (UKS) Di SD Negara Banjar Jaya Kecamatan Tungkal Jaya Kabupaten Musi Banyuasin - Rahmawati, Anggun Rahmawati; Oktavidiati, Eva; Samidah, Ida; Yanuarti, Riska (Avicenna: Jurnal Ilmiah, 2025)
Background: This study investigates how the School Health Program (UKS) is implemented at Banjar Jaya Elementary School, Tungkal Jaya District, Musi Banyuasin Regency. The UKS program is crucial for making schools a healthy environment and supporting student development. Method: This study used a descriptive qualitative approach that employed observation, interviews, and documentation. Results: The results indicate that Banjar Jaya Elementary School has implemented health education effectively and in accordance with the UKS implementation guidelines. Students receive regular curricular health education throughout the learning process to improve their knowledge and healthy living behaviors. Extracurricular health education is also implemented through pre- and post-school cleaning duties, as well as family medicinal plant (toga) duties before lessons begin. School health services include training in handling minor injuries for students and providing first aid for minor accidents. In the promotive aspect, the school actively conducts health outreach and has trained 20 students as little doctors. Conclusion: Meanwhile, the preventive aspect focuses on disease management and provides education on the UKS Triad. Overall, the UKS program at Banjar Jaya Elementary School has been implemented optimally and supports efforts to improve student health. Keywords: UKS, Health Services, Health Education.